Mothers of young children during the COVID-19 pandemic: depressive symptoms and perceived stress - Woll-Weber, Christian F. J.; Reck, Corinna; Marx, Anton K.G.; Küçükakyüz, Su Mevsim; Müller, Mitho; von Tettenborn, Alexandra; Nonnenmacher, Nora; Zietlow, Anna-Lena (Psychopathology, 2025)
Objective: Due to the COVID-19 pandemic, psychosocial well-being of families and parents worldwide has been impaired. As part of a larger online survey, we analyzed maternal depressive symptoms and perceived stress. Method: A total of 666 mothers from Germany with young children (mostly aged 0-3 years) filled out the Edinburgh Postnatal Depression Scale (EPDS) and the Perceived Stress Scale (PSS) at 2 time points during the pandemic (T1: summer/fall 2020; T2: early spring 2021). We (1) calculated prevalence rates of a risk for depression and high perceived stress levels, (2) analyzed differences between time points via paired t tests, and (3) examined the reciprocal relation between the two constructs via cross-lagged panel modeling. Results: Considering cut-off values of the EPDS (≥10) and PSS (≥27), 33.8% carried a risk for depression and 15.2% high levels of stress at T1, whereas, respectively, 55.1% and 26.0% did so at T2. Depressive symptom severity and perceived stress levels significantly differed between measurement points with higher values at T2 (p < 0.001). Our cross-lagged panel analysis revealed large correlations (p < 0.001) within as well as small to medium (i.e., [0.21, 0.47]) auto-regressive (p < 0.001) and reciprocal (p < 0.001) predictions across time points between the severity of depressive symptoms and perceived stress. Conclusions: This work demonstrates how severely mothers of infants were affected by depressive symptoms and perceived stress in a time of pandemic crisis. Psychosocial support should focus on screening and treating mothers as early as possible to mitigate the risk for subsequent depressive symptoms and perceived stress. Aiming attention at both depressive symptom reduction and stress relief most successfully promotes maternal well-being.
Gesehen am 19.08.2025